FASILITAS BELAJAR DAN MOTIVASI BELAJAR SISWA SMA: UJI COBA VALIDITAS DAN RELIABILITAS - Dinda Melati, Puji; Janati, Salsabila; Mika; Puspita Rini, Eko (LPPM STAI Muhammadiyah Probolinggo, 2024)
The study aims to find out how learning facilities influence student learning motivation. Education plays an important role in human resource development, and learning facilities are identified as factors that can affect the quality of learning. Through quantitative research methods, data was collected from 32 students using questionnaires that cover variables of learning facilities and learning motivation. The results of the data analysis showed that there was a relationship between students' perceptions of learning facilities and their level of learning motivation. The validity and reliability of the research instruments have been well tested. The conclusions of this study support theories that emphasize the importance of learning facilities in creating a conducive learning environment. Thus, improved learning facilities are expected to have a positive impact on student learning motivation.